Serial position effects for acoustic stimuli among children with and without hearing loss. - Jutras B (American Journal of Audiology, 2006)
PURPOSE: This study investigated serial position effects on auditory sequential organization among children with hearing loss and with normal hearing. METHOD: Forty-eight children were divided into 4 equally sized groups: 2 groups of 6-7-year-olds and 2 groups of 9-10-year-olds. Each age group had 12 children with normal hearing and 12 children with sensorineural hearing loss. Participants were asked to reproduce auditory sequences of verbal (syllables /ba/ and /da/) and nonverbal (1-kHz pure tone and a wideband noise) elements by pressing associated buttons. RESULTS: No evidence of a recency effect was found, but a primacy effect was observed in the participants' performance under most experimental conditions. Normal hearing participants in the 6-7-year-old group were better at reproducing 3 to 5 verbal items than their counterparts with hearing loss, independent of item sequence position. CONCLUSION: Results suggest that, regardless of hearing status, all children use similar mnemonic strategies.